2003
DOI: 10.1021/bi0349017
|View full text |Cite
|
Sign up to set email alerts
|

The Peptide Antibiotic Clavanin A Interacts Strongly and Specifically with Lipid Bilayers

Abstract: In this study the interaction of the antimicrobial peptide clavanin A with phosphatidylcholine bilayers is investigated by DSC, NMR, and AFM techniques. It is shown that the peptide interacts strongly and specifically with the lipids, resulting in increased order-disorder phase transition temperatures, phase separation, altered acyl chain and headgroup packing, and a drastically changed surface morphology of the bilayer. These results are interpreted in terms of clavanin-specific interactions with lipids and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 37 publications
3
23
1
4
Order By: Relevance
“…The clavanin A MICs for E. coli and S. aureus shown here were higher than those described in the literature (Ͻ10 M) (13,27,28). Apparently this is due to the fact that clavanin A presents better activity in environments containing elevated NaCl concentrations and a more acidic pH (14).…”
Section: Discussioncontrasting
confidence: 50%
“…The clavanin A MICs for E. coli and S. aureus shown here were higher than those described in the literature (Ͻ10 M) (13,27,28). Apparently this is due to the fact that clavanin A presents better activity in environments containing elevated NaCl concentrations and a more acidic pH (14).…”
Section: Discussioncontrasting
confidence: 50%
“…Under these pH conditions, the protonation of these residues will have the overall effect of increasing the cationicity or decreasing the anionicity of the parent molecule, thereby enhancing its ability to target and interact with negatively charged components of microbial membranes. Typical examples include hebraein [224] and clavanins [70,71,72,73,74,75], and in the case of Ci-PAP-A22 and Ci-MAM-A24, it appears that the histidine mediated variation in the cationicity of these peptides facilitates optimal interaction with target microbial membranes on a species-specific basis [61,62]. However, given the high incidence of histidine residues in the antimicrobial molecules reviewed here, it is worth noting that the possession of these residues is not necessarily sufficient for a pH dependent mode of antimicrobial action.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it was found that clavaspirin and clavanins possessed pH dependent antibacterial and antifungal activity [65,66,67,76] with low pH, enhancing the ability of these AMPs to adopt α-helical structure and permeabilize the membranes of these organisms [68,69]. It appeared that the protonation of histidine residues under low pH conditions promoted the ability of these AMPs to target microbial membranes whilst the presence of their glycine and phenylalanine residues provided them with the conformational flexibility and structural hydrophobicity to facilitate bilayer partitioning [70,71,72,73,74,75]. Styelins, which are rich in phenylalanine residues, were found to show activity against both human bacterial pathogens and marine bacteria, such as Psychrobacter immobilis and Planococcus citreus , [68,217].…”
Section: An Overview Of Ph Dependent Peptides and Proteins With Anmentioning
confidence: 99%
“…The exposed hydrophobic patches on the surface of AMPs preferentially move into a hydrophobic environment, in this case the lipid tail region of the phospholipid bilayer, anchoring the peptide into the hydrophobic core of the bilayer and promoting the peptide insertion into the bacterial cell membrane. The deep insertion into membrane results in the largest distortion of the lipid packing in the bilayer and significant changes in the lipid phase transition parameters (Van Kan, Ganchev et al, 2003) Maybe once an effective concentration of MDpep9 is reached, the hydrophobic patch on MDpep9 will insert into the lipid bilayer and cause the plasma membrane to break apart leading to cell death.…”
Section: Antimicrobial Activity and Hemolytic Activitymentioning
confidence: 99%